Improvement of the detectivity in an Fe–Sn magnetic-field sensor with a large current injection. (1st May 2022) - Shiogai, Junichi; Jin, Zhenhu; Satake, Yosuke; Fujiwara, Kohei; Tsukazaki, Atsushi
Abstract: A ferromagnetic nanocrystalline Fe–Sn is an excellent platform for magnetic-field sensor based on anomalous Hall effect (AHE) owing to simple fabrication and superior thermal stability. For improvement of the magnetic-field sensitivity, doping impurity and increasing injection current are effective approaches. However, in the light of magnetic-field detectivity, the large current may increase the voltage noise. In this study, a maximum allowable current was improved by employing the overlayer electrode configuration on a Ta-doped Fe–Sn AHE sensor. In noise measurements, the 1/ f noise becomes significant with increasing the current at low frequency, resulting in saturation of the detectivity to 240 nTHz −1/2 at 120 Hz. At high frequency, the detectivity reaches 48 nTHz −1/2 at 3.1 mA showing ten times improvement of the detectivity compared with the non-doped Fe–Sn AHE sensor. Material design and device structure optimization will accelerate further improvement of the sensing properties of the Fe–Sn-based AHE sensor.